7 Efficacy of Pharmacologic Therapy for Patent Ductus Arteriosus Closure in Preterm Newborns According to Their Gestational Age-Specific Z-Score for Birth Weight. (29th October 2021) - Srivastava, Ankur; Soraisham, Amuchou; Murthy, Prashanth; Kaur, Sharandeep; Kamaluddeen, Majeeda; Thomas, Sumesh; Stritzke, Amelie; Al-Awad, Essa; Mohammad, Khorshid
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Preterm infants who are also intrauterine growth restricted (IUGR) experience more frequent and earlier hemodynamic consequences of patent ductus arteriosus (PDA). This may be related to altered levels of prostaglandins or altered number or sensitivity of their receptors in IGUR infants. Few studies have examined the efficacy of pharmacologic therapy (non-steroidal anti-inflammatory drugs [NSAIDs]: indomethacin, ibuprofen, or acetaminophen) for PDA closure among preterm infants based on their degree of IUGR with differing results. Objectives: Primary: To determine if the degree of IUGR [defined by birth weight (BW) z-score] affects the efficacy of pharmacologic PDA closure and rate of surgical PDA ligation in preterm infants. Secondary: To compare the side effects of NSAIDs and neonatal outcomes based on the severity of IUGR. Design/Methods: This retrospective cohort study included infants of < 30 weeks' GA, admitted to a tertiary neonatal intensive care unit (NICU) between 2010 and 2018, with hemodynamically significant PDA and treated with NSAIDs. Infants with major congenital anomalies, those who received prophylactic Indomethacin and those who died in the first 48 hours were excluded. Birth weight (BW) z-scores were calculated using Olsen nomograms and classified into 3 categories: z-score > −0.5 (normal), z-score −0.5 to −2.0 (mild to moderate growth restriction), z-score <−2 (severe IUGR). We compared responses to NSAID treatment and PDA ligation. Multivariate logistic regression analysis was done to examine the association of BW z-score and response to pharmacological therapy and subsequent surgical PDA ligation. Results: Of the 1511 eligible infants, 769 (51%) had a diagnosis of PDA. Of 517 included infants, 323 (62.5%) had BW z-score >− 0.5, while 154 (29.8%) had z-scores − 0.5 to −2.0 and 40 (7.7%) had z-score < −2. Table 1 shows their demographic characteristics. Efficacy of first course of NSAIDs was not different among these birth weight groups (Table 2). There was no difference in the side effects and neonatal morbidities amongst the three groups (Table 2). Multivariate logistic regression analysis after controlling for GA, gender, antenatal steroids, C-section, and SNAP II showed that the odds of PDA ligation was significantly higher among infants with BW z-score < −2 (aOR 2.68, 95% CI 1.13- 6.36) but not among infants with z-score −0.5 to−2.0 (aOR 1.41, 95% CI 0.84, 2.39) as compared to z-score >-0.5. Conclusion: Preterm severe IUGR infants with z-score < −2 have an associated increased risk of PDA ligation following pharmacologic treatment as compared to normally grown infants.